Towards a quantum ready workforce: the updated European Competence Framework for Quantum Technologies - Greinert, Franziska; Müller, Rainer; Goorney, Simon; Sherson, Jacob; Ubben, Malte S. (Frontiers in Quantum Science and Technology, 2023)
The European Competence Framework for Quantum Technologies is rapidly evolving into the basic common language for educational efforts, comparison of training offerings, mapping of courses and development of educational modules. It has been compiled within the European Quantum Flagship coordination and support projects QTEdu and QUCATS. It is central e.g. in the European Quantum Readiness Center and will be the starting point for a European certification scheme to standardise industry training.For version 2.0, released in April 2023, the framework has been updated and extended, e.g. with descriptions of the proficiency levels A1 to C2. The framework is structured into eight domains with 42 subdomains, each covering several topics and subtopics. This report briefly documents the update process and the role of the framework in quantum technology education.